Mass Customisation: Designed in China, Produced Globally. (2nd November 2017) - Ma, Steven
Abstract : Given the right level of creativity and entrepreneurship, designing for customised 3D printing can offer highly profitable business opportunities anywhere in the world. Xuberance is a case in point. Set up in Shanghai in 2014, the firm's innovative approach to working in both business‐to‐business and consumer markets has earned it huge international recognition and commercial success in an astoundingly short time. Cofounder and Chief Design OfficerSteven Ma outlines the journey so far.